2014
DOI: 10.3390/en7074601
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Performance and Carbon Deposition Differences between the Bi-Layer Interconnector and Conventional Straight Interconnector Solid Oxide Fuel Cell

Abstract: Carbon deposition considered in a solid oxide fuel cell (SOFC) model may be influenced by the operating voltage, inlet water/methane ratio, working temperature and pressure, inlet molar fraction of fuel and so on. The effects of these parameters in a planar SOFC implementing a novel bi-layer interconnector are not well understood. This paper is focused on the numerical study of carbon deposition and electrical performance of a bi-layer interconnector planar SOFC. The results illustrate that the electrical perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Yan et al [9] modelled numerically degradation of the performance of solid oxide fuel cells due to carbon deposition. They found that the bilayer interconnect that they were testing was more robust under carbon deposition than a conventional interconnect, and that the performance of the cell only degraded slightly due to carbon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [9] modelled numerically degradation of the performance of solid oxide fuel cells due to carbon deposition. They found that the bilayer interconnect that they were testing was more robust under carbon deposition than a conventional interconnect, and that the performance of the cell only degraded slightly due to carbon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the proposed tortuosity expression might be helpful for the optimization electrode microstructure to reduce the concentration polarization and further improve SOFC performance. Cross-section of the first typical path S 2 Cross-section of the second typical path S t Total cross section area of the tortuous paths N Molar flux c up pc bot q Molar concentration of gas at the top (bottom) surface of representative volume element…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, significant strides have been made in improving SOFC performance [1][2][3]. In other words, for a given operating voltage, the output current density has been increased drastically.…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2017, 10,1932 10 of 20 moisture and cold gas. For a more specific analysis, cross sections of the middle span of the rotor are shown, such as A to A and B to B.…”
Section: Thermal-fluid Characteristicsmentioning
confidence: 99%
“…Frequent component replacement, owing to pressure drop in the GGH, is caused by plugging and fouling and makes it difficult to operate the power plant. Many related studies have been investigated to avoid the plugging phenomenon, and attempts have been made to reduce plugging by periodically operating a soot blower that uses steam or air in an effective manner [10,11]. However, recently, a case was reported in which the heating element was broken by the strong pressure of the steam or air of the soot blower.…”
Section: Introductionmentioning
confidence: 99%